Anatomical Predictors of Flared Limb Complications in Endovascular Aneurysm Repair. (August 2019) - Pini, Rodolfo; Faggioli, Gianluca; Indelicato, Giuseppe; Gallitto, Enrico; Mascoli, Chiara; Abualhin, Mohammad; Stella, Andrea; Gargiulo, Mauro
Purpose: To evaluate possible predictors of complications with flared iliac stent-graft limbs for ectatic common iliac arteries (CIAs) associated with abdominal aortic aneurysms treated with endovascular aneurysm repair (EVAR).Materials and Methods: A retrospective comparative analysis was conducted of 533 EVAR patients (mean age 75 years; 442 men) treated between 2012 and 2017 who had complications associated with the stent-graft limbs (n=1066). Complications, including type Ib endoleak, type IIIa endoleak, and limb occlusion, were compared between patients with nondilated (<16 mm) CIAs treated with standard iliac limbs (SLs, n=808) vs patients with ectatic CIAs treated with flared limbs (FLs, n=258). Follow-up included a duplex scan at 3, 6, and 12 months and yearly thereafter; computed tomography angiography was performed in case of iliac complications. Risk factors for iliac complications in FLs were investigated using Cox regression and Kaplan-Meier analyses; results of the regression analysis are presented as the hazard ratio (HR) and 95% confidence interval (CI).Results: Overall, no iliac complications occurred at 30 days, but over a mean follow-up of 38±8 months, there were 10 (1%) events (4 limb occlusions, 6 type Ib endoleaks): 7 (3%) in FLs and 3 (0.4%) in SLs (p=0.20). Kaplan-Meier analysis found no differences at 5 years in SLs vs FLs for freedom from limb occlusion (99%±1% vs 98%±1%, respectively; p=0.30) or type Ib endoleak (96%±3% vs 97%±1%, respectively; p=0.44). Similarly, the overall 5-year iliac complication rates were similar in SLs vs FLs (96%±3% vs 95%±2%, p=0.21). Regression analysis found CIA length ≤30 mm (HR 4.7, 95% CI 1.02 to 21.6, p=0.04) and a diameter ≥20 mm (HR 7.8, 95% CI 1.05 to 64.8, p=0.03) to be independent predictors of iliac complications in FLs. Kaplan-Meier estimates of iliac complication–free survival in FLs were significantly worse when the CIA length was ≤30 mm (79%±9% vs 98%±1%, p=0.003) or the diameter was ≥20 mm (85%±7% vs 99%±1%, p=0.02). The combination of both risk factors produced significantly poorer iliac complication–free survival compared with cases in which there was one or no risk factor (67%±19% vs 96%±2% vs 99%±1%, respectively; p<0.001).Conclusion: Iliac limb complications are infrequent in EVAR, regardless of the type of iliac limb chosen; however, CIAs ≤30 mm in length or ≥20 mm in diameter significantly increased the risk of late iliac complications in FLs. If both characteristics were present, this risk was further elevated.